1986
DOI: 10.1200/jco.1986.4.12.1740
|View full text |Cite
|
Sign up to set email alerts
|

Behenoyl cytosine arabinoside, daunorubicin, 6-mercaptopurine, and prednisolone combination therapy for acute myelogenous leukemia in adults and prognostic factors related to remission duration and survival length.

Abstract: Fifty-one consecutive previously untreated adult patients with acute myelogenous leukemia (AML) were treated with BHAC-DMP (N4-behenoyl-I-beta-D-arabinofuranosyl-cytosine, daunorubicin, 6-mercaptopurine, and prednisolone) therapy. Forty-two patients (82.4%) achieved complete remission (CR). The Kaplan-Meier analysis revealed a probability for remaining in remission of 14% and for survival of 23% at 6 years. Pretreatment factors related to the achievement of CR, such as age, French-American-British (FAB) classi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

1989
1989
2011
2011

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 19 publications
0
17
0
Order By: Relevance
“…In the JALSG protocol, it takes approximately 2 years to complete the chemotherapy from the remission induction through the consolidation and maintenance therapy. 1 In the protocol for AML in JALSG, the duration of therapy is very long and cyclophosphamide and prednisolone are used in the maintenance therapy. These drugs may influence the lymphocytes subsets especially at the early period after chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the JALSG protocol, it takes approximately 2 years to complete the chemotherapy from the remission induction through the consolidation and maintenance therapy. 1 In the protocol for AML in JALSG, the duration of therapy is very long and cyclophosphamide and prednisolone are used in the maintenance therapy. These drugs may influence the lymphocytes subsets especially at the early period after chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 With the use of techniques such as polymerase chain reaction (PCR), minimal residual disease (MRD) can be detected at an early stage after chemotherapy in the patients who are in complete remission (CR). Some investigators show that the elimination of MRD detected by PCR is not always necessary for long-term survival, 3 however, it has been also shown that patients with a higher level of MRD appeared to have an increased chance of relapse and that MRD disappears in conjunction with the duration of CR in some patients with acute leukemia.…”
Section: Introductionmentioning
confidence: 99%
“…BHAC-DM-based regimen was a response-oriented individualized chemotherapy regimen using BHAC, dounorbicin (DNR) and 6-mercaptppurine (6-MP). [35][36][37][38] All patients obtained complete remission by induction therapies. For post-remission consolidation, BHAC-based and HDACbased regimens were administered in 14 and 12 cases, respectively.…”
Section: Clinical Characteristics Of Patients With T(8;21) Amlmentioning
confidence: 99%
“…Kimura et al [9] reported that 35% of leukemic patients treated achieved com plete remission, in the phase II study of BH-AC. Moreover, BH-AC combined with daunomycin, 6-mercaptopurine or vincristine is effective for treating human leukemia [10,11]. Patients with gastroin testinal or breast cancer respond better to treatment with a combination of mitomy cin C (MMC), 5-fluorouracil (5-FU) and BH-AC, than to MMC and 5-FU alone [12], hence, BH-AC is effective for treating solid tumors, under conditions of com bined chemotherapy.…”
Section: Discussionmentioning
confidence: 99%